Immediate effects of the central posteroanterior mobilization technique on pain and range of motion in patients with mechanical neck pain - Rotsalai Kanlayanaphotporn (2014)
PURPOSE: To determine the immediate effects of the central posteroanterior (PA) mobilization technique on both pain and active cervical range of motion in patients with mechanical neck pain presenting with central or bilateral symptoms.